2009
DOI: 10.5194/acp-9-8331-2009
|View full text |Cite
|
Sign up to set email alerts
|

VOC measurements within a boreal forest during spring 2005: on the occurrence of elevated monoterpene concentrations during night time intense particle concentration events

Abstract: Abstract. In this study we present measurements of selected trace gases and aerosols made in a boreal forest during the BACCI-QUEST IV intensive field campaign in Hyytiälä, Finland in April 2005. Springtime diel and vertical variations of VOCs are discussed in connection with the variations in other trace gases and with the prevailing meteorological conditions. A daytime and a nighttime event have been analysed in detail. The nighttime particle event occurred synchronously with huge increases in monoterpenes, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 69 publications
4
68
3
Order By: Relevance
“…Figure 7B shows that psp-polarized SFG spectra of particles collected in the PM1 size fraction during the early spring at the same field site yield little to no signal above the noise. Work by Eerdekens et al 186 shows generally smaller monoterpene concentrations in the 0.06−0.18 ppbv during the colder period of their early April 2005 study than in this present work (Table 1). A similar study by Liao et al 187 carried out during several periods including early March 2007 shows monoterpene concentrations between 0.01 and 0.1 ppbv, with episodic (hourlong) concentration spikes rising as high as 1 to 2 ppbv.…”
Section: Natural Aerosol Particles Formed Incontrasting
confidence: 59%
“…Figure 7B shows that psp-polarized SFG spectra of particles collected in the PM1 size fraction during the early spring at the same field site yield little to no signal above the noise. Work by Eerdekens et al 186 shows generally smaller monoterpene concentrations in the 0.06−0.18 ppbv during the colder period of their early April 2005 study than in this present work (Table 1). A similar study by Liao et al 187 carried out during several periods including early March 2007 shows monoterpene concentrations between 0.01 and 0.1 ppbv, with episodic (hourlong) concentration spikes rising as high as 1 to 2 ppbv.…”
Section: Natural Aerosol Particles Formed Incontrasting
confidence: 59%
“…High mixing ratios of terpenoids in airmasses that have passed over the sawmill have been documented frequently (Eerdekens et al, 2009;Sinha et al, 2010;Hakola et al, 2012;Nölscher et al, 2012 on the 14 th of September from 06:30 to 08:00 UTC, HYSPLIT back-trajectories (GDAS global, 0.5°), indicating that the air mass passed over Korkeakoski ≈ 0.5 hours prior to reaching the SMEAR II site.…”
Section: Type 3 Nightsmentioning
confidence: 99%
“…The NO 3 gradient is the result of lower production rates close to the ground, where O 3 levels are depleted due to deposition and also lower loss rates aloft as the concentration of 5 reactive traces gases from ground level emissions decreases with altitude. High resolution data (Brown et al, 2007b) indicate that the largest gradient in NO 3 concentration is often found in the lowermost 50 m. Night-time monoterpene mixing ratios in forested, boreal regions have been found to display a vertical gradient, with highest mixing ratios at lower levels (Holzinger et al, 2005;Rinne et al, 2005;Eerdekens et al, 2009). This is a result of direct emissions of e.g.…”
Section: Vertical Gradient In No 3 Reactivitymentioning
confidence: 99%
See 2 more Smart Citations